Šolska knjižnica OŠ Franceta Prešerna Črenšovci v projektu bralne pismenosti - Litrop, Nataša (Šolska knjižnica, 2013)
France Prešeren Primary School Črenšovci has in the school year 2011/12 entered the project Empowering pupils through improvement of reading literacy and access to knowledge. A priority task in the operational plan was the systematic development of pupils' reading literacy and increase in their reading motivation. The school library has also been actively included in this project through its activities and introduction of various reading (learning) strategies.
Keywords: bralna pismenost; branje; osnovne šole; OŠ Franceta Prešerna Črenšovci; projekti; šolske knjižnice